Glibenclamide alleviates inflammation in oleic acid model of acute lung injury through NLRP3 inflammasome signaling pathway - Chen H; Ding Y; Chen W; Feng Y; Shi G (Dove Medical Press, 2019)
Hong Chen,1,2 Yongjie Ding,1,2 Wei Chen,1,2 Yun Feng,1,2 Guochao Shi1,21Department of Respiration and Critical Care Disease, Ruijin Hospital, School of Medicine, Shanghai Jiaotong University, Shanghai 20025, People’s Republic of China; 2Institute of Respiratory Diseases, School of Medicine, Shanghai Jiaotong University, Shanghai 20025, People’s Republic of ChinaBackground: Pulmonary fat embolism (PFE) is one of the important causes of acute lung injury (ALI), but its pathogenesis is unclear. In recent years, it has been found that the NLRP3 inflammasome is closely related to inflammatory response. However, there are no reports about the involvement of NLRP3 in PFE- associated ALI. Glibenclamide is a kind of hypoglycaemic drug with anti-inflammatory effect. It has been reported to have the anti-inflammatory effect related to inhibiting NLRP3.Objective: To determine whether NLRP3 inflammasome was involved in ALI induced by PFE or whether glibenclamide had therapeutic effects on such lung injury, we designed this experiment.Materials and methods: The rat model of intravenous injection of oleic acid (OA) was used to simulate PFE. Rats were divided into three groups: control, OA and glibenclamide treatment group. Blood free fatty acid (FFA) concentration was determined by ACS-ACOD. Histopathological examinations were taken to assess the severity of lung injury. The expression of NLRP3 pathway and its downstream products were analyzed by IHC, WB, qPCR and ELISA.Results: Four hours after intravenous OA injection, the typical pathological manifestations of ALI accompanied by elevated levels of plasma FFAs were found. The activity of NLRP3 inflammasomes increased in OA group, too. Pretreatment with glibenclamide partly inhibited the increase in NLRP3, caspase-1 and IL-1β expression induced by OA, simultaneously attenuated the lung injury. But it has little effect on the expression of Toll-like receptor 4 (TLR4) expression in this experiment.Conclusion: NLRP3 inflammasome, one of the main components of innate immune response, involved in ALI induced by OA. Glibenclamide can alleviate this kind of ALI by inhibiting rather the NLRP3/caspase-1/IL-1β signaling pathway than the levels of FFAs or TLR4 pathway.Keywords: glibenclamide, oleic acid, acute lung injury, oxidative stress, NLRP3 inflammasome